Psychological aspects of hippotherapy for children with severe neurological impairment: An exploratory study - Karin Hediger; Marina Lunzenfichter; Eva Markzoll; Wanda Arnskötter; Martina Schaudek; Gerhard Kluger (PLoS ONE, 2025)
Background and objectives Neuropediatric hospitalization presents significant psychological challenges that affect quality of life, learning, and treatment adherence. Hippotherapy might address these factors, but its psychological effects are underexplored. This paper explores the psychological and neuropsychological potential of hippotherapy in pediatric neurorehabilitation. Objectives include analyzing (1) patient characteristics, (2) session characteristics, (3) patients’ psychological and neuropsychological reactions, and (4) therapists’ perceptions of the extent to which the therapeutic goals were realized in the sessions. Methods This retrospective explorative study examines data from 581 children and adolescents (M =  9.01 years, SD =  3.88) with severe neurological disorders who underwent hippotherapy. We used the registration form for each patient and session-documentation forms for each hippotherapy session. We extracted information regarding patient and session characteristics, performed a content analysis on the documented reactions of the patients and the predefined neuropsychosocial goals set by the rehabilitation team, and examined to what extent the goals were met during hippotherapy. The data were analyzed using descriptive statistics. Results Patients received an average of 3.47 hippotherapy sessions. During hippotherapy, 66.4% of the predefined goals were reached; cognitive functions and social behavior were the most successfully achieved goals. The most frequently documented patient reaction was had fun (81% of all sessions). Conclusion Our study shows that hippotherapy is a feasible and beneficial treatment for neuropediatric patients with severe neurological impairments. The goals of hippotherapy can be much broader than the usually targeted physical functioning and mobility. Hippotherapy might be especially effective in promoting fun and motivation and in addressing patients’ socioemotional needs.